Differential price‐responsiveness of smoking behaviors among non‐Hispanic African Americans and non‐Hispanic whites in the United States. (17th April 2021) - Wang, Yingning; Max, Wendy; Yao, Tingting; Keeler, Courtney; Sung, Hai‐Yen
Abstract: Background and aims: Non‐Hispanic African Americans (African Americans) smoke fewer cigarettes per day (CPD) and are more likely to be non‐daily smokers than non‐Hispanic whites (whites). Little is known about how changes in cigarette prices might contribute to these differences. This study aimed to measure the price‐responsiveness of smoking participation, non‐daily smoking among current smokers and smoking intensity among daily or non‐daily smokers for African Americans and compare the price‐responsiveness estimates with those for whites. Design: Analysis of data from the 2009–14 National Adult Tobacco Surveys and cigarette price data from the Tax Burden on Tobacco report. Setting: United States. Participants: A total of 19 232 African American and 197 939 white adults aged 18+. Measurements: We used a three‐part econometric model of cigarette demand to estimate the price‐responsiveness of smoking participation, daily versus non‐daily smoking and smoking intensity. The model controlled for secular variation, state‐level anti‐smoking sentiment and smoke‐free air laws and socio‐demographics. Findings: In 2009–14, 20.2% of African Americans and 17.7% of whites identified as current smokers; 70.2% of African American smokers and 81.4% of white smokers smoked daily. The price elasticity of smoking participation was significant for whites at −0.16 [95% confidence interval (CI) = –0.23, –0.09], indicating that a 10% increase in prices would reduce smoking participation by 1.6%, but not statistically significant for African Americans, and this racial/ethnic differential price responsiveness was not statistically significant. The price elasticity of smoking intensity was statistically significant for African American daily smokers at −0.29 (95% CI = −0.42, –0.16), but not statistically significant for white daily smokers, and this racial/ethnic differential price‐responsiveness was statistically significant. The price elasticity of daily versus non‐daily smoking among current smokers, and the price elasticity of smoking intensity among non‐daily smokers were not statistically significant for either racial/ethnic group. Conclusion: In the United States, cigarette price increases may have stronger effects on decreasing daily smokers' consumption among African Americans than among non‐Hispanic whites.